Quality of life and its influencing factors in patients with acute coronary syndrome - Mohsen Taghadosi; Leila Ghanbari-Afra; Monireh Ghanbari-Afra; Hamid Reza Gilasi (Tehran University of Medical Sciences, 2017)
Background & Aim: Acute coronary syndrome (ACS) is a life-threatening condition. Considerable doubts exist over the effects of this disease on patients' quality of life (QOL). The aim of this study was to Survey QOL and its influencing factors in patients with ACS. Methods & Materials: A convenience sample of 300 patients with ACS was drawn from Shahid Beheshti Hospital, Kashan, Iran, to this cross-sectional study. Sampling was performed from March to September 2014. We employed the Short Form Health Survey Questionnaire for gathering the data. Study data were analyzed by conducting the descriptive parameters, the one-way ANOVA test and the independent-samples t-test as well as logistic regression analysis using the SPSS version 13.0. Results: The means of QOL in patients with ACS were 56.30 ± 17.15. The QOL Score in mental and physical component were 61.15 ± 19.46 and 51.57 ± 24.56, respectively. However, the logistic regression showed that male gender [odds ratio (OR): 1.88, confidence interval (CI): 1.04-3.43], coronary stenosis < 50% (OR: 3.25, CI: 1.48-7.13), and normal ejection fraction (OR: 3.41, CI: 1.31-8.89) increase the QOL (P < 0.050). Conclusion: The results of this study showed that the QOL in patients with ACS is low. Female gender, low ejection fraction and coronary stenosis over 50% causes of reduction in their QOL. Hence, it is recommended that in nursing care during hospitalization and after discharge attend these problems.